Allelic variation for broad-spectrum resistance and susceptibility to bacterial pathogens identified in a rice MAGIC population - Bossa Castro, Ana M.; Tekete, Cheick; Raghavan, Chitra; Delorean, Emily E.; Dereeper, Alexis; Dagno, Karim; Koita, Ousmane; Mosquera Cifuentes, Gloria Maria; Leung, Hei; Verdier, Valerie M.; Leach, Jan E. (Wiley, 2018)
Quantitative trait loci (QTL) that confer broad‐spectrum resistance (BSR), or resistance that is effective against multiple and diverse plant pathogens, have been elusive targets of crop breeding programmes. Multiparent advanced generation intercross (MAGIC) populations, with their diverse genetic composition and high levels of recombination, are potential resources for the identification of QTL for BSR. In this study, a rice MAGIC population was used to map QTL conferring BSR to two major rice diseases, bacterial leaf streak (BLS) and bacterial blight (BB), caused by Xanthomonas oryzae pathovars (pv.) oryzicola (Xoc) and oryzae (Xoo), respectively. Controlling these diseases is particularly important in sub‐Saharan Africa, where no sources of BSR are currently available in deployed varieties. The MAGIC founders and lines were genotyped by sequencing and phenotyped in the greenhouse and field by inoculation with multiple strains of Xoc and Xoo. A combination of genomewide association studies (GWAS) and interval mapping analyses revealed 11 BSR QTL, effective against both diseases, and three pathovar‐specific QTL. The most promising BSR QTL (qXO‐2‐1, qXO‐4‐1 and qXO‐11‐2) conferred resistance to more than nine Xoc and Xoo strains. GWAS detected 369 significant SNP markers with distinguishable phenotypic effects, allowing the identification of alleles conferring disease resistance and susceptibility. The BSR and susceptibility QTL will improve our understanding of the mechanisms of both resistance and susceptibility in the long term and will be immediately useful resources for rice breeding programmes